Peroxisome proliferator‐activated receptor gamma agonists in the prevention and treatment of murine systemic lupus erythematosus. Issue 3 (July 2014) - Aprahamian, Tamar R.; Bonegio, Ramon G.; Weitzner, Zachary; Gharakhanian, Raffi; Rifkin, Ian R.
Summary Peroxisome proliferator‐activated receptor gamma (PPARγ) agonists are known to have many immunomodulatory effects. We have previously shown that the PPARγ agonist rosiglitazone is beneficial when used early in prevention of disease in murine models of systemic lupus erythematosus (SLE) and SLE‐related atherosclerosis. In this report, we demonstrate that another PPARγ agonist, pioglitazone is also beneficial as a treatment for early murine lupus, indicating that this is a class effect and not agent‐specific. We further attempt to define the ability of PPARγ agonists to ameliorate established or severe autoimmune disease using two mouse models: the MRL.lpr SLE model and the gld.apoE−/− model of accelerated atherosclerosis and SLE. We demonstrate that, in contrast to the marked amelioration of disease seen when PPARγ agonist treatment was started before disease onset, treatment with rosiglitazone after disease onset in MRL.lpr or gld.apoE−/− mice had minimal beneficial effect on the development of the autoimmune phenotype; however, rosiglitazone treatment remained highly effective at reducing lupus‐associated atherosclerosis in gld.apoE−/− mice after disease onset or when mice were maintained on a high cholesterol Western diet. These results suggest that beneficial effects of PPARγ agonists on the development of autoimmunity might be limited to the early stages of disease, but that atherosclerosis, a major cause of death in SLE patients, may be ameliorated even in established or severe disease.